Crusoe’s Broken Window: A tribute to Frédéric Bastiat - Schneider, Christian (REVISTA PROCESOS DE MERCADO, 2017)
Frédéric Bastiat was a great economist1 and writer, but most of all, he deserves everlasting fame as an educator. His 1850 essay «The Broken Window»2 teaches an unforgettable lesson. Unforgettable, on the one hand, because it is humiliating: humiliating to realize that one had not grasped an idea so simple yet so crucial for a basic understanding of economics. Unforgettable, on the other hand, be-cause once we have learned to «turn the mind’s eye to those hid-den consequences of human actions, which the bodily eye does not see» (Bastiat [1850] 2011a, 43), an intriguing journey of discovery begins. It has rightly been called «the one lesson»3 to which all economics can be reduced: to think through not only the visible and immediate consequences of human action and interaction, but also the unseen effects: those which are not yet seen, and those which will never be seen because they would follow only from an alternative course of action.4 Another sign of Bastiat’s excellence is that he was the first econ-omist to make extensive use of thought experiments with one or a few actors only, named, and sometimes ridiculed as, «Robinson Crusoe economics». In the imaginary laboratory of the desert is-land, we are free to set arbitrary conditions. In particular, we can construct the simplest version of any problem, where the essential features stand out most clearly. Simple scenarios, as Henry Hazlitt ([1946] 2008, 91) notes, «are ridiculed most by those who most need them, who fail to understand the particular principle illustrated even in this simple form, or who lose track of that principle com-pletely when they come to examine the bewildering complications of a great modern economic society». These complications can be mastered best by extending the analysis step by step from one ac-tor to a higher number, until real-world complexity is sufficiently approximated.5 When Bastiat was writing his last work That Which is Seen, and That Which is Not Seen, he was suffering from a terminal illness closing in on him. We can only speculate what form it might have taken and how much more he could have achieved, had he been granted more time. But what is obvious in the work he did is the importance of Crusoe scenarios and of that which remains unseen. The thought experiments presented in what follows merely com-bine these two ideas. Thus, this essay is deeply inspired by Basti-at’s way of thinking, and hopes to do honor to his inspiration.